A theoretical investigation of the effects of solar eclipses on the ionosphere - Walker, Anthony David Mortimer (Rhodes University, Faculty of Science, Department of Physics, 1962)
The behaviour of the ionosphere during a solar eclipse is of great interest because radiation from the sun is the cause of ionization in the upper atmosphere and it is useful to be able to conduct experiments where this radiation is cut off and restored in a known manner. Experimental results, especially those dealing with the F2 layer, have proved puzzling. Cusps which cannot be explained appear on the records obtained from ionosphere sounders and in the F2 region the electron density at a given height shows a maximum after the eclipse where one would expect it simply to rise to a steady value. An attempt is made in this thesis to explain some of the anomalies in terms of tilts in the ionospheric layers and minima of electron density or "valleys" between the ionospheric layers. The problem is attacked theoretically. Part I deals with the theoretical background to ionospheric physics in general and to this problem in particular. Standard methods of dealing with radio propagation in the ionosphere as well as some methods developed by the author are discussed. Part II deals directly with the effects of a solar eclipse on a theoretical ionosphere. Ionograms which would be obtained in the theoretical ionosphere are constructed. These are scaled by standard methods to show where errors may arise . It appears that tilts in the layers have only a small effect. The effect of the valley is, however, extremely important, giving rise to the apparent maximum of electron density in the F2 layer at a given height after the eclipse. This maximum does not in fact exist but arises from an error in the scaling method which ignores the possibility of a valley. Some records taken during the solar eclipse of 25 December, 1954 have been scaled. They support the conclusion reached theoretically.
Keywords: Solar eclipses; Ionosphere; Solar activity